Tuning humidity for highly selective detection of methanol and 2-butanone using MOF-derivatives NiO microrods - Theodoro, Reinaldo S. [UNESP]; Sá, Bruna S. [UNESP]; Perrone, Olavo M. [UNESP]; Perfecto, Tarcísio M.; Volanti, Diogo P. [UNESP] (Springer Nature, 2023)
Industrialization has brought about significant challenges to human well-being, primarily due to the emission of toxic volatile organic compounds (VOCs). Therefore, there is considerable interest and need to detect these VOCs with high selectivity and reproducibility. In this context, developing VOC sensing devices for continuous environmental monitoring and ensuring well-being is crucial. One way to produce inexpensive sensors with reasonable detection limits and selectivity is by using semiconductor metal oxides. Furthermore, they can withstand relative humidity variations in the detection process, which is still a significant challenge. In this study, we present a sensor based on NiO microrods derived from the decomposition of nickel-metal-organic frameworks (Ni-MOF) using microwave-assisted solvothermal (MAS) and thermal decomposition methods. The NiO microrods exhibited highly selective in detecting methanol (Response = 143 ± 27%) under dry atmospheric conditions and 2-butanone (Response = 119 ± 16%) under wet atmospheric conditions (43% RH) at a working temperature of 150 °C. In addition, the NiO sensor presented a relatively fast response time for detecting methanol (78 s) and 2-butanone (36 s) under optimal working conditions. Therefore, selectively modulating the relative humidity during the sensor analysis process, the NiO microrods act as a dual-mode sensor for methanol and 2-butanone.